ENHANCING SPEAKING COMPETENCE BY INTENSIFYING ENGLISH LEARNING STRATEGY FOR PHARMACY STUDENTS ON FIRST GRADE OF STIKES AL FATAH BENGKULU IN 2025/2026 ACADEMIC YEARS - Suci Dwina Darma; Nanik Nanik; Khodijah Khodijah (JOLADU: Journal of Language Education, 2026)
This research was designed to establish of enhancing for students’ oral communication skills were developed by intensifying English usage in class. In this research, a pre experimental design involving one group with pre test and post test was used, and speaking tests were administered to collect the data. The sample of this research consisted of students in first semester at STIKES Al Fatah Bengkulu that involved a total of 36 students. A comparative technique was employed to examine and compare student’s scores prior to and following the speaking activity. The findings of the research showed that students’ speaking proficiency in vocabulary from 2.5 increased to 3.84 with improvement was 53.2% and the students’ speaking competence in pronunciation from 2.33 increased to 3.75% with improvement was 60.94% by totally mean score was 57.07%. Moreover, for speaking competence was effective with the result of the statistical analysis using t-test value and t-table value was proved 20.92>2.030. It meant that t-test value was higher than t-table value. It can be concluded that pharmacy students got a positive impact and feasible method for applied by using an intensifying English learning strategy of students in first semester at STIKES Al Fatah.